Tuning the accessibility and activity of Au25(SR)18 nanocluster catalysts through ligand engineering - Li, Jingguo; Nasaruddin, Ricca Rahman; Feng, Yan; Yang, Jun; Yan, Ning; Xie, Jianping (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2016)
In this work, the effects of thiolate ligands (-SR, e.g., chain length and functional moiety) on the accessibility and catalytic activity of thiolate-protected gold nanoclusters (e.g., Au25(SR)18) for 4-nitrophenol hydrogenation is reported. The data suggest that Au25(SR)18 bearing a shorter alkyl chain shows a better accessibility to the substrates (shown by shorter induction time, t0) and a higher catalytic activity (shown by higher apparent reaction rate constant, kapp). The functional moiety of the ligands is another determinant factor, which clearly suggests that ligand engineering of Au25(SR)18 would be an efficient platform for fine-tuning its catalytic properties.